Sports Marketing and Management: Strategies for Success in the Digital Age - Gheorghe JINGA (Revista de Management Comparat International)
In the digital age, the intersection between marketing and sports management becomes increasingly relevant to the success of sports organizations. This article addresses the evolution and complex dynamics between these two areas, emphasizing the need for innovative and adaptable strategies. Through a comparative analysis of traditional versus digital methodologies, the study highlights how technology, data analysis, and the digital engagement of fans represent critical levers in building strong sports brands and generating sustainable revenue. Exploring various digital marketing tactics — including social media, content marketing, and augmented reality — the article showcases how they can be leveraged to maximize fan engagement and loyalty. Additionally, the critical role of effective management is discussed, highlighting how advanced data analysis and technological innovations can improve sports performance and organizational operations. Through selected case studies, the paper illustrates practical applications of the discussed theories, thus providing an applied perspective and knowledge base for practitioners in the field. In conclusion, the article proposes a series of strategic recommendations, underscoring the importance of continual adaptation to the changing digital landscape to ensure success and sustainability in the sports world. This work aspires to serve as a valuable resource for both researchers and professionals in the fields of marketing and sports management.